Análisis de la calidad del servicio y su incidencia en la satisfacción del cliente, de la empresa INCAVIT - Corral Bravo, Sonia Yuliana (2025)
Service quality is considered a crucial factor for competitiveness and organizational success, especially in service-oriented industries. In this context, the present research focuses on analyzing the relationship between service quality and customer satisfaction at the company INCAVIT S.A. The study followed a qualitative-quantitative methodology, combining both types of methods for data collection and analysis. A validated questionnaire was used to assess customer perceptions across the entire client portfolio, and the 5W+2H matrix was applied to structure strategic proposals for the company. The results show that INCAVIT S.A. maintains a high level of customer satisfaction in key areas such as product quality, facilities, and clarity in communication. However, areas for improvement were also identified, particularly in staff training to better understand customer needs, and in updating equipment and technologies to enhance perceived service quality. In conclusion, the study highlights the need to adopt strategic measures that address these findings in order to improve overall service quality.